Pembelajaran Sejarah Berbasis Sejarah Lokal Peran Blitar dalam Mempertahankan Kemerdekaan Indonesia 1948-1950 - Widiadi, Aditya Nugroho; Sulistyo, Wahyu Djoko; Ayundasari, Lutfiah; Sapto, Ari; Nur Habibi, Muhammad Aqib; Nur Hafida, Mellina; Ashari, Gedhe; Dewi, Edna Sari Kusuma (Jayapangus Press, 2024)
This study analyses Blitar's role as one of the Republic of Indonesia's guerrilla bases during the Dutch military aggression period and the struggle for independence. Located in East Java, Blitar has a long history, starting from the Dutch colonial period, the Japanese occupation, to the post-proclamation of Indonesian independence. Blitar became an important centre for military and emergency government activities in East Java, especially after the Dutch launched Military Aggression I and II. This research illustrates how Blitar became a gathering place for long march troops from various regions, as well as the formation of a military government structure that played an important role in defending the sovereignty of the Republic of Indonesia. Using data from various sources, including official reports and historical studies, this research seeks to present a picture of the socio-political and military dynamics in Blitar during this critical time in Indonesian history. However, despite its significant role, local history studies related to Blitar's role in this struggle are still minimally explored in history learning in schools. Therefore, the integration of Blitar's local history in the curriculum is expected to strengthen students' understanding of the importance of their region's contribution to national history.